2020
DOI: 10.1021/acsami.0c05812
|View full text |Cite
|
Sign up to set email alerts
|

Boosted Charge Transfer in Twinborn α-(Mn2O3–MnO2) Heterostructures: Toward High-Rate and Ultralong-Life Zinc-Ion Batteries

Abstract: Aqueous ZIBs are one of the most promising nextgeneration rechargeable batteries because of the high capacity, high hydrogen evolution overpotential, and chemically stable reversible plating/stripping of the zinc electrode in the mild aqueous electrolyte. However, there are limited cathode materials that can store Zn 2+ reversibly with superior cycling and rate capability. Herein, hierarchically porous nanorods composed of twinborn α-(Mn 2 O 3 −MnO 2 ) heterostructures are proposed as a robust cathode for Zn s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 63 publications
(105 reference statements)
3
47
0
Order By: Relevance
“…It can be seen that elemental Bi, Mn, and O signals are detected in HIP‐Bi‐600 and HIP‐Bi‐500, while only Mn and O elements exist in HIP‐0‐600 and HIP‐0‐500. In the high‐resolution Mn 2p spectra of HIP‐Bi‐600, three sets of spin‐orbit‐resolved peaks can be resolved as Mn 4+ (2 p 1/2 , 654.8 eV; 2 p 3/2 , 643.5 eV); Mn 3+ (2 p 1/2 , 653.8 eV; 2 p 3/2 , 642.3 eV) and Mn 2+ (2 p 1/2, 652.6 eV; 2 p 3/2 , 640.9 eV), indicating the existence of the manganese mixed phase, which is consistent with literature [25] . Similarly, HIP‐0‐600 and HIP‐0‐500 electrodes also display three pairs of peaks.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It can be seen that elemental Bi, Mn, and O signals are detected in HIP‐Bi‐600 and HIP‐Bi‐500, while only Mn and O elements exist in HIP‐0‐600 and HIP‐0‐500. In the high‐resolution Mn 2p spectra of HIP‐Bi‐600, three sets of spin‐orbit‐resolved peaks can be resolved as Mn 4+ (2 p 1/2 , 654.8 eV; 2 p 3/2 , 643.5 eV); Mn 3+ (2 p 1/2 , 653.8 eV; 2 p 3/2 , 642.3 eV) and Mn 2+ (2 p 1/2, 652.6 eV; 2 p 3/2 , 640.9 eV), indicating the existence of the manganese mixed phase, which is consistent with literature [25] . Similarly, HIP‐0‐600 and HIP‐0‐500 electrodes also display three pairs of peaks.…”
Section: Resultssupporting
confidence: 91%
“…synthesized α‐MnO 2 /Mn 2 O 3 composite cathode by a molten salt method. This research indicated that Mn 2 O 3 nanoparticles were obtained by a phase transform from α‐MnO 2 nanobelts and the α‐MnO 2 /Mn 2 O 3 composite with the largest mass ratio of Mn 2 O 3 delivers the best electrochemical performance of 162 mAh g −1 at 3 A g −1 and a capacity retention of 86.2 % after 1000 cycles when assembled with modified Zn−C anode [25,26] . Compared to the two‐phase separated composite, a twinborn MnO 2 /Mn 2 O 3 heterojunction reported by Long et al.…”
Section: Introductionmentioning
confidence: 79%
“…In addition, an outstandingly high specic energy of 628 W h kg À1 was obtained for Zn-doped ZIBs. This is a very high specic capacity and specic energy, clearly surpassing those of most MnO 2 -based and other cathode materials, such as a-(Mn 2 O 3 -MnO 2 ) heterostructures, 32 metalorganic framework Cu 3 (HHTP) 2 , 33 oxygen defect enriched (NH 4 ) 2 V 10 O 25 nanosheets, 34 graphene-wrapped MnO/C, 35 etc., as shown in Table S2. † The two sloping plateaus can be mainly attributed to the redox reactions of Mn 4+ /Mn 3+ and Mn 3+ /Mn 2+ , respectively, which are in accordance with the cyclic voltammetry observations.…”
Section: Electrochemical Characterizationmentioning
confidence: 96%
“…set the cathode with long-cycle life, large specific capacity and high energy density. [28] Here, we provide an available cooperation of multivariate manganese oxide coated by carbon hybrids (MnO 2 /MnO@C and MnO 2 / Mn 3 O 4 @C) via plasma-assisted milling for Zn-ion cathode, in which multivariate manganese oxide materials convert their instinct electron structures to boost the kinetic ability of ions (Zn 2+ and H + ) insertion/ desertion while the carbon substrates further enhanced the electrical conductivity of MnO x nanocrystals. Especially, the MnO 2 /MnO@C hybrid owns the phase stability behavior due to the available cooperation of Mn (II) and Mn (IV) phases during the reaction of metal ions converting to the metastable state with Zn 2+ / H + insertion into the manganese oxides, which accelerates ion/electron migration rates and promotes charge storage.…”
Section: Introductionmentioning
confidence: 99%